Dealing with disagreement: The depolarizing effects of everyday diplomatic skills face-to-face and online. (September 2022) - Roos, Carla Anne; Koudenburg, Namkje; Postmes, Tom
In online text-based discussions, people behave less diplomatically because they are more outspoken and less responsive. This can feed impressions of polarization. This article uses a new methodology to isolate the influence of outspokenness and responsiveness in shaping perceptions of polarization in online chat and face-to-face discussions. Text-based online and face-to-face discussions were reproduced in a face-to-face format (Study 1) and in a text-based chat format (Study 2). Uninformed observers (N = 102 and N = 103, repeated measures) evaluated these. The results showed that responsiveness was generally considered indicative of agreement and good social relationships but the interpretation of outspokenness (or lack of ambiguity) depended on the medium format. This suggests that what counts as diplomacy is not the same for each medium. Moreover, the experiences of the actors reproducing the chats in a face-to-face format highlighted the differences between media. We conclude that online conversational dynamics may play an important role in societal polarization.